Core concepts of human rights and inclusion of vulnerable groups in the mental health policies of Malawi, Namibia, and Sudan - MAC LACHLAN, MALCOLM (My University, 2013)
Abstract Background: One of the most crucial steps towards delivering judicious and comprehensive mental health care is the formulation of a policy and plan that will navigate mental health systems. For policy-makers, the challenges of a high-quality mental health system are considerable: the provision of mental health services to all who need them, in an equitable way, in a mode that promotes human rights and health outcomes. Method: EquiFrame , a novel policy analysis framework, was used to evaluate the mental health policies of Malawi, Namibia, and Sudan. The health policies were assessed in terms of their coverage of 21 predefined Core Concepts of human rights (Core Concept Coverage), their stated quality of commitment to said Core Concepts (Core Concept Quality), and their inclusion of 12 Vulnerable Groups (Vulnerable Group Coverage). In relation to these summary indices, each policy was also assigned an Overall Summary Ranking, in terms of it being of High , Moderate ,or Low quality. Results: Substantial variability was identified across EquiFrame ’ s summary indices for the mental health policies of Malawi, Namibia, and Sudan. However, all three mental health policies scored high on Core Concept Coverage. Particularly noteworthy was the Sudanese policy, which scored 86% on Core Concept Coverage, and 92% on Vulnerable Group Coverage. Particular deficits were evident in the Malawian mental health policy, which scored 33% on Vulnerable Group Coverage and 47% on Core Concept Quality, and was assigned an Overall Summary Ranking of Low accordingly. The Overall Summary Ranking for the Namibian Mental Health Policy was High ; for the Sudanese Mental Health Policy was Moderate ; and for the Malawian Mental Health Policy was Low . Conclusions: If human rights and equity underpin policy formation, it is more likely that they will be inculcated in health service delivery. EquiFrame may provide a novel and valuable tool for mental health policy analysis in relation to core concepts of human rights and inclusion of vulnerable groups, a key practical step in the successful realization of the Millennium Development Goals.
PUBLISHED
Corresponding author
Keywords: Mental health policy, Core concepts of human rights, Vulnerable groups, Malawi, Namibia, Sudan; Mental health policy, Core concepts of human rights, Vulnerable groups, Malawi, Namibia, Sudan